Rethinking marine infrastructure policy and practice: Insights from three large-scale marina developments in Seattle. (March 2015) - Wilson, A. Meriwether W.; Mugerauer, Robert; Klinger, Terrie
Abstract: The global transformation of the marine nearshore is generating profound losses of ecological and geomorphological functions and ecosystem services, as natural environments are replaced with built. With conservation a diminishing option and restoration often unrealistic, there is a need to rethink development and the potential for marine infrastructure to contribute to net environmental gain. Through analysis of 150 years of change associated with the development of three large-scale marinas in the Seattle area, this research identifies the ways in which evolving policy frameworks and ecological understanding determine the nature, efficiency and environmental outcomes of coastal marine developments. Decisions on infrastructure design, mitigation strategies and policy interpretations directly determined the ecological fate of marine biota inhabiting these structures as well as surrounding ecosystems. In spite of increasing evidence of environmental legislation driving mitigation and innovative engineering, the net ecological trajectories remained negative. There were no tested demonstrations of marine mitigation to confirm which measures would succeed. Where scientific understanding existed, the uptake into planning and legislation was slow. More broadly, this research highlights a need and opportunity to consider marine infrastructure as living laboratories to inform a policy shift from a no-net-loss paradigm to net-environmental-gain. This evolution is timely, with sea level rise requiring new approaches to coastal defenses and with marine energy infrastructure increasingly being located offshore, where there is little knowledge of the ecological changes occurring in both time and space. Highlights: Urbanization of coastal marine habitats is resulting in loss of ecological function. Policy frameworks for coastal infrastructure have become increasingly complex. Scientific understanding of built marine habitats is inadequate to inform design. No-net-loss paradigm provides limited incentive for environmental enhancement. Marine infrastructure as in-situ laboratories to inform policy and practice.